Metallic Iron for Environmental Remediation: The Fallacy of the Electron Efficiency Concept - Hu, Rui; Ndé-Tchoupé, Arnaud Igor; Cao, Viet; Gwenzi, Willis; Noubactep, Chicgoua (Frontiers in Environmental Chemistry, 2021)
The suitability of remediation systems using metallic iron (Fe0) has been extensively discussed during the past three decades. It has been established that aqueous Fe0 oxidative dissolution is not caused by the presence of any contaminant. Instead, contaminant reductive transformations are a consequence of Fe0 oxidation. Yet researchers are still maintaining that electrons from the metal body are involved in the process of contaminant reduction. According to the electron efficiency concept, electrons from Fe0 should be redistributed to: (i) contaminants of concern (COCs), (ii) natural reducing agents (e.g. H2O, O2), and/or (iii) reducible co-contaminants (e.g. NO3-). The electron efficiency is defined as the fraction of electrons from Fe0 oxidation which is utilized for the reductive transformations of COCs. This concept is in frontal contradiction with the view that Fe0 is not directly involved in the process of contaminant reduction. This communication recalls the universality of the concept that reductive processes observed in remediation Fe0/H2O systems are mediated by primary (e.g. FeII, H/H2) and secondary (e.g. Fe3O4, green rusts) products of aqueous iron corrosion. The critical evaluation of the electron efficiency concept suggests that it should be abandoned. Instead, research efforts should be directed towards tackling the real challenges for the design of sustainable Fe0-based water treatment systems based on fundamental mechanisms of iron corrosion.